The Effect of Islamicity Performance Index, Intellectual Capital, Operational Efficiency Ratio, and Non-Performing Financing on Return on Assets - Nurriski, Aulia; Rizkiyah, Putri (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to obtain empirical evidence on the influence of Islamicity Performance Index (proxied by profit sharing ratio), intellectual capital, operational efficiency ratio, and non-performing financing on return on assets. Design/methodology/approach – This study uses quantitative research. It utilizes secondary data. The population is 14 Sharia Commercial Banks listed on the Financial Services Authority in Indonesia between 2022 and 2024. The sample is 11 Sharia Commercial Banks listed on the Financial Services Authority in Indonesia between 2022 and 2024. The total number of observations in this study is 33. The analysis technique used to test the hypotheses is multiple regression analysis using Eviews9 software. Findings – The results of this study indicate that the profit-sharing ratio variable has a negative and significant effect on return on assets. The intellectual capital has a negative and insignificant effect on return on assets. The operational efficiency ratio has a negative and insignificant effect on return on assets. The non-performing financing has a negative and significant effect on return on assets. Research limitations/implications – This study was conducted only on Sharia Commercial Banks in Indonesia during the period 2022-2024. The findings provide insights based on secondary data obtained from the banks’ annual financial statements and are expected to be useful for management, regulators, and future researchers in understanding factors affecting profitability in Sharia banking. JEL: M41, G21, G32